Chemical compositions of essential oils, antimicrobial effect and antioxidant activity studies of Hyoscyamus niger L. from Türkiye - Inci, Şule; Sancar, Pelin Yılmaz; Demirpolat, Azize; Kırbağ, Sevda; Civelek, Şemsettin (Pamukkale University, 2025)
This study investigated the essential oil components of Hyoscyamus niger L. and their antimicrobial and antioxidant properties. Essential oils were extracted separately from the aerial parts and seeds of the plant using the hydrodistillation method. Antimicrobial activity was evaluated using the disk diffusion method, while antioxidant activity was assessed by measuring the total antioxidant status (TAS), total oxidant status (TOS), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity. The primary essential oil components of the aerial parts were identified as phytol (52.09%) and hexahydrofarnesyl acetone (19.66%). Hydrodistillation of the seeds yielded 0.7% (v/w) yellow oils, comprising 41 components that accounted for 99.0% of the oil. The major components in the seed oils were hexahydrofarnesyl acetone (46.36%) and hexanal (9.05%). Methanol extracts of the aerial parts demonstrated inhibitory effects on pathogenic microorganisms, with inhibition zones ranging from 13±0.46 to 32±0.11 mm. The TAS and TOS values of the methanol extracts were calculated as 3.77±0.0 mmol and 6.94±0.0 ?mol, respectively. The DPPH radical scavenging activity increased with rising extract concentrations. These findings highlight the potential antimicrobial and antioxidant applications of H. niger essential oils and methanol extracts. © 2025 Pamukkale University. All rights reserved.
Keywords: Antimicrobial and antioxidant activity; Essential oil composition; Hyoscyamus niger L; Türkiye